STATUS PENCEMARAN DI PERAIRAN CILINCING, PESISIR DKI JAKARTA - Anna Rejeki Simbolon (Jurnal Pro-Life, 2016)
Cilincing Waters is one of the coastal area of Jakarta with environmental pressures continue to increase. Put waste originating from anthropogenic activities increasingly concerned about the condition of waters in the region. This study aims to determine the status of pollution in the waters of Cilincing, Coastal Jakarta. Measurement of physical-chemical parameters of the water were analyzed descriptively based on quality standards used are based on the Decree of the Minister of Environment No. 51 of 2004 on marine water quality standard for marine purposes. Analysis of the pollution status can be approximated by using STORET contained in Appendix II Decree of the Minister of Environment No. 115 of 2003 regarding guidelines for the determination of water quality status. The results obtained from this study indicate that the levels of COD in the Waters Cilincing ranged between 119,86 mg / l to 398,01mg / l. While the DO levels ranged from 3,67 mg / l to 4,53 mg / l and BOD levels ranged from 32,1 mg / l to 35,47 mg / l. These indicate that the status of pollution in waters classified as contaminated Cilincing were grading DO, COD and BOD has exceeded quality standards based on Decree of the Minister of Environment No. 51 of 2004 on marine water quality standard for marine purposes. Keywords: status of pollution, water Cilincing, storet